Hinduism in India: the early period - Bailey, Greg; Oddie, Geoffrey A. (Hinduism in India, 2017)
Introduction / Greg Bailey -- Hinduism Contextualized / Greg Bailey -- Rituals / Axel Michaels -- The Mahābhārata and Dharma / Adam Bowles -- Mythology / Greg Bailey -- Religious Pathways : Social and Ritual Activity (karman), Knowledge (jñana), and Devotion (bhakti) / Angelika Malinar -- Hindu Theology / Eric John Lott -- Making Space for the Sacred : Hindu Art and Material Religion / Crispin Branfoot